Considerações sobre a Sudesul: formação e modernização territorial - Breno Viotto Pedrosa (Confins)
Starting from the historical context of twentieth century first half, is elucidated central government aspires to develop and integrate the southwestern border of Brazil. It provoked planning experiences, which are later captured and expanded to the entire South region, aiming at regional development with the creation of Sudesul. This institution was a tool to reinforce measures that promoted agriculture and agribusiness, promoting exports and increasing food production as a basis for increasing other industrial sectors and social welfare. It is noted that the plans were concatenated with the central planning guidelines and according to political, economic, regional and international interests.